2018
DOI: 10.1007/s12034-017-1544-4
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting epitaxial $$\hbox {YBa}_{2}\hbox {Cu}_{3}\hbox {O}_{7-\delta }$$ YBa 2 Cu 3 O 7

Abstract: Thin films of optimally doped(001)-oriented YBa 2 Cu 3 O 7−δ are epitaxially integrated on silicon(001) through growth on a single crystalline SrTiO 3 buffer. The former is grown using pulsed-laser deposition and the latter is grown on Si using oxide molecular beam epitaxy. The single crystal nature of the SrTiO 3 buffer enables high quality YBa 2 Cu 3 O 7−δ films exhibiting high transition temperatures to be integrated on Si. For a 30-nm thick SrTiO 3 buffer, 50-nm thick YBa 2 Cu 3 O 7−δ films that exhibit a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Copyright 2018, The Authors, published by AIP Publishing LLC YBCO/STO/Si structure showing c) the entire stack (inset shows a close‐up of the YBCO/STO interface) and d) resistivity–temperature curves showing the critical superconducting temperature in comparison to YBCO grown on STO substrates (insets shows a close‐up of the transition region). Reproduced with permission . Copyright 2018, Springer Nature.…”
Section: Materials and Functional Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2018, The Authors, published by AIP Publishing LLC YBCO/STO/Si structure showing c) the entire stack (inset shows a close‐up of the YBCO/STO interface) and d) resistivity–temperature curves showing the critical superconducting temperature in comparison to YBCO grown on STO substrates (insets shows a close‐up of the transition region). Reproduced with permission . Copyright 2018, Springer Nature.…”
Section: Materials and Functional Propertiesmentioning
confidence: 99%
“…Ahmadi‐Majlan et al demonstrated the integration of YBa 2 Cu 3 O 7–δ (YBCO) on Si using STO‐buffered (001) Si . The 30 nm thick STO buffer was grown by MBE, upon which a 50 nm thick film of YBCO was grown by PLD.…”
Section: Materials and Functional Propertiesmentioning
confidence: 99%